Sarcomatous Meningioma: Diagnostic Pitfalls and the Utility of Molecular Testing. Issue 8 (12th June 2021) - Lucas, Calixto-Hope G; Devine, Patrick; Solomon, David A; Giannini, Caterina; Reifenberger, Guido; Dahiya, Sonika; Caccamo, Dario; Perry, Arie
Abstract: Anaplastic meningiomas can have a sarcomatous appearance on histology but true sarcomatous (metaplastic) differentiation is rare. These tumors follow an aggressive clinical course with recurrence and poor clinical outcomes. Due to significant overlap in morphology and immunohistochemical profiles, distinguishing between sarcomatous transformation of a meningioma and a true sarcoma can be challenging. Here, we outline potential diagnostic pitfalls and the utility of ancillary molecular testing in 3 patients diagnosed with sarcomatous meningiomas. We report loss of typical meningothelial markers in sarcomatous meningiomas. Ancillary molecular testing can support the diagnosis of sarcomatous meningioma when a molecular signature consistent with meningioma is seen, such as inactivation of the NF2 gene. Recognition of this rare transformation in meningioma can prevent a misdiagnosis of a primary sarcoma, whether sporadic or radiation-induced from prior treatment of a more classic meningioma.